David S. Miller: scientist, mentor, friend - a tribute and thank you - Bauer, Björn; Renfro, J. Larry; Karnaky, Karl J.; Masereeuw, Rosalinde; Fricker, Gert; Cannon, Ron E.; Hartz, Anika (Fluids and barriers of the CNS, 2020)
David S. Miller was Acting Scientific Director of the Division of Intramural Research at the National Institute of Environmental Health Sciences, National Institutes of Health, and Head of the Intracellular Regulation Group in the Laboratory of Toxicology and Pharmacology before he retired in 2016. David received his Ph.D. in biochemistry from the University of Maine in 1973. David was a Group Leader at the Michigan Cancer Foundation before joining the NIEHS in 1985. His research covered a wide range from renal excretory transport mechanisms to regulation of transporters at the blood-CSF and blood-brain barriers, from fish, amphibians and birds to mammals. David was an outstanding scientist with irresistible enthusiasm for science and an incredible ability to think outside the box while being an exceptional mentor and friend.